YLT-11, a novel PLK4 inhibitor, inhibits human breast cancer growth via inducing maladjusted centriole duplication and mitotic defect. Issue 11 (November 2018) - Lei, Qian; Xiong, Lu; Xia, Yong; Feng, Zhanzhan; Gao, Tiantao; Wei, Wei; Song, Xuejiao; Ye, Tinghong; Wang, Ningyu; Peng, Cuiting; Li, Zhongping; Liu, Zhihao; et al.
Abstract Polo-like kinase 4 (PLK4) is indispensable for precise control of centriole duplication. Abnormal expression of PLK4 has been reported in many human cancers, and inhibition of PLK4 activity results in their mitotic arrest and apoptosis. Therefore, PLK4 may be a valid therapeutic target for antitumor therapy. However, clinically available small-molecule inhibitors targeting PLK4 are deficient and their underlying mechanisms still remain not fully clear. Herein, the effects of YLT-11 on breast cancer cells and the associated mechanism were investigated. In vitro, YLT-11 exhibited significant antiproliferation activities against breast cancer cells. Meanwhile, cells treated with YLT-11 exhibited effects consistent with PLK4 kinase inhibition, including dysregulated centriole duplication and mitotic defects, sequentially making tumor cells more vulnerable to chemotherapy. Furthermore, YLT-11 could strongly regulate downstream factors of PLK4, which was involved in cell cycle regulation, ultimately inducing apoptosis of breast cancer cell. In vivo, oral administration of YLT-11 significantly suppressed the tumor growth in human breast cancer xenograft models at doses that are well tolerated. In summary, the preclinical data show that YLT-11 could be a promising candidate drug for breast tumor therapy.